The countercyclical capital buffer: A cross-country overview of policy frameworks - Elif C. Arbatli-Saxegaard; Mohammad Adnan Muneer (Norges Bank, 2020)
The countercyclical capital buffer (CCyB) is a relatively new macroprudential tool, but the number of countries that have set a positive buffer level increased significantly over recent years. Furthermore, during the Covid-19 crisis, many countries released their countercyclical capital buffers, marking the first time that the CCyB was used widely in a downturn. In this paper, we provide a comprehensive and systematic overview of the international design of CCyB frameworks, covering a broad set of experiences from 33 countries. We have identified five key areas of focus for our analysis of CCyB frameworks: 1) institutional framework and the use of buffers; 2) objectives and policy over the financial cycle; 3) use of the Basel credit gap and Basel guide; 4) the information basis for setting the buffer; and 5) communication strategy. The frameworks outlined by designated authorities have already started to evolve and it is likely that this will continue as more experience is gained. This paper can be a useful input in that process, summarizing country practices in a comprehensive set of areas relevant for the CCyB policy.
hdl:11250/2678931
Keywords: 330; Antizyklische Finanzpolitik; Coronavirus; Finanzkrise; Welt